2013
DOI: 10.1111/1574-6941.12086
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate limitation induces the intergeneric inhibition ofPseudomonas aeruginosabySerratia marcescensisolated from paper machines

Abstract: Phosphate is an essential nutrient for heterotrophic bacteria, affecting bacterioplankton in aquatic ecosystems and bacteria in biofilms. However, the influence of phosphate limitation on bacterial competition and biofilm development in multispecies populations has received limited attention in existing studies. To address this issue, we isolated 13 adhesive bacteria from paper machine aggregates. Intergeneric inhibition of Pseudomonas aeruginosa WW5 by Serratia marcescens WW4 was identified under phosphate-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The bacterial strain Serratia marcescens WW4 was isolated from a paper machine in Taiwan (1). Phenotypic characterization of this bacterium revealed that it is capable of forming biofilms individually or with Pseudomonas aeruginosa .…”
Section: Genome Announcementmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial strain Serratia marcescens WW4 was isolated from a paper machine in Taiwan (1). Phenotypic characterization of this bacterium revealed that it is capable of forming biofilms individually or with Pseudomonas aeruginosa .…”
Section: Genome Announcementmentioning
confidence: 99%
“…Phenotypic characterization of this bacterium revealed that it is capable of forming biofilms individually or with Pseudomonas aeruginosa . Intriguingly, while the two bacteria may coexist in LB medium or M9 minimal medium, phosphate limitation can induce intergeneric inhibition of P. aeruginosa by S. marcescens WW4 (1). …”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…S. marcescens WW4 was originally isolated from environmental water samples in a paper factory in Taiwan. 6 Escherichia coli DH5a (Takara Bio, Shiga, Japan) and E. coli BL21-CodonPlus (DE3)-RIP (Agilent Technologies, Santa Clara, CA) were used as hosts for recombinant plasmids and proteins, respectively. Plasmids pSTV28 (Takara) and pQE2 (Qiagen, Tokyo, Japan) were used for cloning of aac(6¢)s and purification of recombinant AAC(6¢)s, respectively, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Serratia marscens strain WW4 are antagonists of Pseudomonas aeruginosa WW5 showing biofilm formation and significantly compromised mortality rate when co-cultured under phosphate-limited conditions with Pseudomonas aeruginosa (Chung et al, 2013;De Queiroz and De Melo, 2006;Kuo et al, 2013). Serratia species are gramnegative bacteria, categorised in the large family of Enterobacteriaceae (Benevides-Matos and Biville, 2010; Moradigaravand et al, 2016;Zaheer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%